THE PROCESS OF BUILDING ETHNIC-RACIAL RELATIONS AND THE TEACHING OF HISTORY: AFFIRMATIVE ACTIONS AT COLÉGIO ESTADUAL RODOLFO DE OLIVEIRA - Andrade , Renart Nelmo; dos Santos , Jean Isídio (Editora Impacto Científico, 2025)
The article presents the actions for implementing the National Curriculum Guidelines for the Education of Ethnic-Racial Relations and for the Teaching of Afro-Brazilian and African History and Culture at Rodolfo de Oliveira State School in the year 2013. Understanding racism and its forms within the classroom setting, and consequently overcoming it through affirmative actions, emerges as an urgent challenge for the school and educators. For this text, bibliographic research and a case study were used to demonstrate the possibilities of implementing Law No. 10,639 of 2003.KEYWORDS: Education of Ethnic-Racial Relations, Law No. 10,639, History Teaching, Racism, Affirmative Actions.DOI: https://doi.org/10.56238/edimpacto2025.092-034